Soft Set Theory for Data Reduction - Amin Luddin, Adnan (2012)
The recent changes in utility structureso development in renewable technologies and increased. There are many data exist all stored data stored in the computer using intemet, everyday data was stored. This data poses a problem when we need to use data" but the data are too numerous and scattered on the internet blur of data. Therefore, there are techniques required and are introduced to overcome this problem. Discussion discussed is Knowledge Discovery in Databases and techniques used are multi-soft set of techniques. Dataset is a set of multi-value data. By using Multi soft sets irq can reduce the data based on the theory of soft sets.